Condensing Mappings and Best Proximity Point Results - Sarah O. Alshehri; Hamed H. Alsulami; Naseer Shahzad (Journal of Mathematics)
Best proximity pair results are proved for noncyclic relatively u-continuous condensing mappings. In addition, best proximity points of upper semicontinuous mappings are obtained which are also fixed points of noncyclic relatively u-continuous condensing mappings. It is shown that relative u-continuity of T is a necessary condition that cannot be omitted. Some examples are given to support our results.